Electricity generation using biogas: study of feasibility in sewage treatment station in Paraná (Research, Society and Development, 2021)
The distributed generation of electricity produced from organic waste is an alternative that requires careful analysis, due to the numerous economic and environmental factors associated with this production process. Considering every human activity consumes natural resources and in the end it results in tailings, urban sewage has aspects which classify it as a waste of high polluting power, and its treatment is necessary to maintain the sustainability of society and the environment, once it removes pollutants from previously used water, returning it to water bodies in good condition, as well as generating biogas if a controlled anaerobic process is used. Biogas offers a potential for electricity generation, thus requiring an assessment of the economic feasibility of using motor generators to take advantage of this natural resource in UASB reactors already installed in sewage treatment plants. The survey of the NPV and the LCOE emerge as appropriate tools. The study evaluated the volume of treated sewage in some cities in the State of Paraná, mainly the relationship between the amount of population served with sewage and its potential for biogas production, and consequently, it’s potential for generating electricity. The evaluation method identified biogas as an economically viable energy resource, according to the result of the city of Curitiba, which obtained a NPV of 87,834,069.69 reais, an IRR of 18.04% am with a 5-month payback, as well as its LCOE value of 34.53 R$/MWh.